Feasibility of a self-rehabilitation program for the upper limb for stroke patients in Benin - NIAMA NATTA, DIDIER; ALAGNIDE, HOUNTONDJI ETIENNE; KPADONOU GODONOU, TOUSSAINT; STOQUART, GAETAN; DETREMBLEUR, CHRISTINE; LEJEUNE, THIERRY (My University, 2015)
Introduction: Stroke is a major cause of disability and represents a very high cost in developing countries. Self-rehabilitation programs represent a new and original treatment for stroke patients, likely to reduce upper limb impairments and improve activity and participation. The goal of this study is to evaluate the feasibility of a self-rehabilitation protocol in Benin. Methods: Twelve chronic stroke patients carried out the upper limb self-rehabilitation program (3 hours/ day, 5 days/week for 2 weeks). The performance of these patients was evaluated before and after the selfrehabilitation program, by measuring the number of exercises that patients were able to achieve during a three-hour session, and by assessing their gross manual dexterity. Results: Twelve patients were effectively able to complete the entire program. The number of unimanual exercises and self-mobilizations performed during a three-hour session as well as the score of the Box and Block test were improved by the self-rehabilitation program (P < 0.05). Discussion and conclusion: Self-rehabilitation programs are feasible and inexpensive as they do not involve a therapist. It is then a promising approach in stroke rehabilitation, particularly in developing countries, where rehabilitation costs are usually supported by patients.
Keywords: Stroke; Rehabilitation; Self-rehabilitation program; Upper limb